The Effect of Group Cooperation and Work Communication on the Performance of State Civil Services - Limega Candrasa; Cia Cai Cen (Jurnal Mantik, 2021)
This research was conducted in the Office of the Secretariat of the Regional People's Representative Council of SerdangBedagai Regency. The purpose of this study was to determine how the influence of work communication on the performance of the State Civil Apparatus at the Sergai Regency Regional Representative Council Office. The results of this study indicate. (1) It can be seen that the value of the adjuted R square is 0.668 or 66.8%, this shows that the group cooperation variable (XI) and the work communication variable (X2) can explain the performance variable (Y) by 66.8%, the rest is 33 , 2% (100% - 66.8%) explained by other variables outside this research model. (2) The results of the t test (partial) show that t count (3.111)> t table (2.039), as well as the significance value of 0.004 <0.05, it can be concluded that the first hypotension is accepted, meaning that the group cooperation variable (X1) has a significant effect on variable (Y). (3) The results of the t test (partial) show that t count (5,515)> t table (2,039), and a significance value of 0.00 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the Work Communication Variable (X2) has a significant effect on Performance Variable (Y). (4) the results of the simultaneous test (F) can be seen that Fcount (33.169)>Ftable (3.32) and a significance value of 0.00 <0.05, it can be concluded that the third hypothesis is accepted, meaning that the Group Cooperation Variable (X1), Variable Work Communication (X2) has a significant effect simultaneously (simultaneously) on the Performance Variable (Y).